An Integrated Omics Approach Uncovers the Novel Effector Ecp20-2 Required for Full Virulence of Cladosporium fulvum on Tomato - Karimi-Jashni, Mansoor; Maeda, Kazuya; Yazdanpanah, Farzaneh; de Wit, Pierre J. G. M.; Iida, Yuichiro (Frontiers in Microbiology, 2022)
The fungus Cladosporium fulvum causes the leaf mould in tomatoes. During the colonization of the host, it secretes plenty of effector proteins into the plant apoplast to suppress the plant’s immune system. Here, we characterized and functionally analyzed the Ecp20-2 gene of C. fulvum using combined omics approaches. RNA-sequencing of susceptible tomato plants inoculated with C. fulvum race 0WU showed strongly induced expression of the Ecp20-2 gene. Strong upregulation of expression of the Ecp20-2 gene was confirmed by qPCR, and levels were comparable to those of other known effectors of C. fulvum. The Ecp20-2 gene encodes a small secreted protein of 149 amino acids with a predicted signal peptide of 17 amino acids. Mass spectrometry of apoplastic fluids from infected tomato leaves revealed the presence of several peptides originating from the Ecp20-2 protein, indicating that the protein is secreted and likely functions in the apoplast. In the genome of C. fulvum, Ecp20-2 is surrounded by various repetitive elements, but no allelic variation was detected in the coding region of Ecp20-2 among 120 C. fulvum isolates collected in Japan. Δecp20-2 deletion mutants of strain 0WU of C. fulvum showed decreased virulence, supporting that Ecp20-2 is an effector required for full virulence of the fungus. Virulence assays confirmed a significant reduction of fungal biomass in plants inoculated with Δecp20-2 mutants compared to those inoculated with wild-type, Δecp20-2-complemented mutants, and ectopic transformants. Sequence similarity analysis showed the presence of Ecp20-2 homologs in the genomes of several Dothideomycete fungi. The Ecp20-2 protein shows the best 3D homology with the PevD1 effector of Verticillium dahliae, which interacts with and inhibits the activity of the pathogenesis-related protein PR5, which is involved in the immunity of several host plants.